2020
DOI: 10.3390/rs12111861
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Applicability of Water Column Correction Models in Optically Complex Coastal Waters

Abstract: Maps of submerged aquatic vegetation (SAV) are of primary importance for the sustainable management of coastal areas and serve as a basis for fundamental ecological studies. Various water column correction (WCC) models are successfully applied in clear Case-1 waters to compensate for the variable water depth effect. The performance of the WCC in less clear Case-2 waters is rarely assessed. In this study, the performance and applicability of model-based WCC algorithms in the complex Baltic Sea were analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Several researchers have found that the removal of the water column influence can improve the accuracy of SAV classification, as well as abundance quantification. 44,55 However, the application of WCC may also have an opposite effect, both in clear and turbid environments. For example, Marcello et al 56 and Mederos-Barrera et al 57 concluded that WCC did not improve the benthic classification results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several researchers have found that the removal of the water column influence can improve the accuracy of SAV classification, as well as abundance quantification. 44,55 However, the application of WCC may also have an opposite effect, both in clear and turbid environments. For example, Marcello et al 56 and Mederos-Barrera et al 57 concluded that WCC did not improve the benthic classification results.…”
Section: Discussionmentioning
confidence: 99%
“…43 Detailed description of Maritorena WCC processing is provided by Vahtmäe et al. 44 In August, we had additional measurements of a and b b from ground-truth stations. The availability of a and b b allowed one to apply Lee WCC model 41 to August S2 imagery.…”
Section: Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other commonly used SAV extraction algorithms, our method cannot extract SAV in areas with large canopy depths and turbid water bodies throughout the year. Due to the high absorption of water molecules in the near-infrared band, SAV with a large canopy depth cannot be detected [30,31]. The water level in Baiyangdian Lake fluctuates greatly.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%